The Role of Principal Leadership Style in Improving the Performance of Public and Private Elementary School Teachers in Bandung Regency - Rizqi, Faturahman; Hadi, Muhammad Sofian; Surizkika, Aldi (Universitas Pahlawan Tuanku Tambusai, 2026)
The performance of elementary school teachers is the foundation of learning quality, but various competency improvement programs are often not optimal because performance issues are also influenced by organizational factors at the school level. The literature still shows a gap in explaining how school principal leadership works through daily